Mouse model reveals the role of RERE in cerebellar foliation and the migration and maturation of Purkinje cells. - Bum Jun Kim; Daryl A Scott (PLoS ONE, 2014)
Nuclear receptors and their coregulators play a critical role in brain development by regulating the spatiotemporal expression of their target genes. The arginine-glutamic acid dipeptide repeats gene (Rere) encodes a nuclear receptor coregulator previously known as Atrophin 2. In the developing cerebellum, RERE is expressed in the molecular layer, the Purkinje cell layer and the granule cell layer but not in granule cell precursors. To study RERE's role in cerebellar development, we used RERE-deficient embryos bearing a null allele (om) and a hypomorphic allele (eyes3) of Rere (Rere(om/eyes3)). In contrast to wild-type embryos, formation of the principal fissures in these RERE-deficient embryos was delayed and the proliferative activity of granule cell precursors (GCPs) was reduced at E18.5. This reduction in proliferation was accompanied by a decrease in the expression of sonic hedgehog (SHH), which is secreted from Purkinje cells and is required for normal GCP proliferation. The maturation and migration of Purkinje cells in Rere(om/eyes3) embryos was also delayed with decreased numbers of post-migratory Purkinje cells in the cerebellum. During the postnatal period, RERE depletion caused incomplete division of lobules I/II and III due to truncated development of the precentral fissure in the cerebellar vermis, abnormal development of lobule crus I and lobule crus II in the cerebellar hemispheres due to attenuation of the intercrural fissure, and decreased levels of Purkinje cell dendritic branching. We conclude that RERE-deficiency leads to delayed development of the principal fissures and delayed maturation and migration of Purkinje cells during prenatal cerebellar development and abnormal cerebellar foliation and Purkinje cell maturation during postnatal cerebellar development.